1990
DOI: 10.1084/jem.171.5.1739
|View full text |Cite
|
Sign up to set email alerts
|

A host gene regulates the structure of the transmembrane envelope protein of murine leukemia viruses.

Abstract: Heterogeneity in the structure of the envelope proteins has been observed in many human and animal retroviruses and may influence pathogenicity. However, the biological significance of this heterogeneity and the mechanisms by which it is generated are poorly understood. We have studied a mouse model in which the envelope gene structure of lymphoma-associated viruses appears to be controlled by a single host gene. The inoculation of HRS and CWD mice with a leukemogenic murine leukemia virus (MuLV) results in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…We had previously shown that the presence of type I or type II recombinants within lymphoma cells is influenced by a host gene located on mouse chromosome 17. In these experiments, the injection of the ecotropic SL3-3 MuLV induced tumors and type I recombinants in HRS/J mice, whereas tumors from injected CWD mice contained type II recombinants (6,32,37). The type I-forming phenotype (TI) of HRS/J mice was dominant with respect to the type II-forming phenotype (TII) of CWD mice and segregated with restriction fragment length polymorphisms on chromosome 17 which are located within the H-2 locus, the mouse major histocompatibility complex.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…We had previously shown that the presence of type I or type II recombinants within lymphoma cells is influenced by a host gene located on mouse chromosome 17. In these experiments, the injection of the ecotropic SL3-3 MuLV induced tumors and type I recombinants in HRS/J mice, whereas tumors from injected CWD mice contained type II recombinants (6,32,37). The type I-forming phenotype (TI) of HRS/J mice was dominant with respect to the type II-forming phenotype (TII) of CWD mice and segregated with restriction fragment length polymorphisms on chromosome 17 which are located within the H-2 locus, the mouse major histocompatibility complex.…”
mentioning
confidence: 97%
“…Animals of these strains express early in life endogenous ecotropic MuLVs that subsequently acquire pathogenic sequences by recombination with endogenous polytropic and xenotropic viruses. Similarly, the injection of exogenous ecotropic MuLVs, such as SL3-3, into these or other susceptible strains induces leukemias and the formation of envelope gene recombinants (6,10,31). The recombinants typically incorporate 5Ј envelope gene sequences from one or more of the 20 or so endogenous polytropic viruses.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of the polytropic recombinant generated during SL3 infection is dependent on the mouse strain serving as host and is influenced by host factors. In HRS/J and CBA/J mice, for example, the dominant selection for type I env recombinants is controlled by a single host gene that is not an endogenous provirus but resides within the major histocompatibility complex (4,10,(12)(13)(14). Both type I and type II env recombinants arise during SL3 infection NIH/Swiss mice (12,14), the strain examined in the present study.…”
mentioning
confidence: 99%